THE ROLE OF ARTIFICIAL INTELLIGENCE IN MANAGEMENT DECISION-MAKING - Oripova, Kamila Ravshanovna (THE INNOVATION ECONOMY, 2026)
This article comprehensively explores the multifaceted role of artificial intelligence (AI) in contemporary management decision-making. It delves into how AI technologies, ranging from machine learning and natural language processing to advanced analytics, are transforming traditional managerial approaches. The paper examines AI’s capability to process vast datasets, uncover hidden patterns, and generate predictive insights, thereby enhancing the accuracy and speed of strategic and operational decisions. It highlights AI’s contribution to automating routine decision-making processes, allowing human managers to focus on higher-level strategic thinking and complex problem-solving. Furthermore, the article discusses how AI optimizes resource allocation, improves risk management by identifying potential threats proactively, and enables a more personalized customer experience through sophisticated data analysis. The integration of AI is presented not merely as a technological upgrade but as a fundamental shift in how organizations perceive, analyze, and act upon information.